2016
DOI: 10.1088/1757-899x/136/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality of Hills Water, Supply Water and RO Water Machine at Ulu Yam Selangor

Abstract: Abstract. The rapid development resulted in the deterioration of the quality of drinking water in Malaysia. Recognizing the importance of water quality, new alternatives for drinking water such as mineral water processing from reverse osmosis (RO) machine become more popular. Hence, the demand for mineral water, natural spring water or water from the hills or mountains rose lately. More consumers believed the quality of these spring water better than other source of drinking water. However, the quality of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…These values aligned with the finding by [6] and [7] for spring water flow from fractures in granite rocks in Semenyih, Malaysia with pH range of 6.7. [6,19] reported that the pH of water sources in hot spring around Selangor, Malaysia is characterized as alkaline, and this might be due to geological composition of the region [8] tested a spring water from the hill of Ulu Yam also shows the pH value for hill water is 6.8 and almost neutral. The pH of water and the amount of TDS are related.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values aligned with the finding by [6] and [7] for spring water flow from fractures in granite rocks in Semenyih, Malaysia with pH range of 6.7. [6,19] reported that the pH of water sources in hot spring around Selangor, Malaysia is characterized as alkaline, and this might be due to geological composition of the region [8] tested a spring water from the hill of Ulu Yam also shows the pH value for hill water is 6.8 and almost neutral. The pH of water and the amount of TDS are related.…”
Section: Resultsmentioning
confidence: 99%
“…Water quality index (WQI) is a measure of the physical, chemical and biological characteristics of water [29]. Recently, several studies have focused on monitoring spring water quality in international [33,35] and Malaysia [6,7,8,9]. In Malaysia, spring water quality evaluation and monitoring have received little attention, therefore, these types of analyses are needed to understand the physiochemical and quality changes of spring water.…”
Section: Introductionmentioning
confidence: 99%
“…Ammoniacal Nitrogen is a water quality parameter that determines the degree of pollution based on the growth of algae. The growth of algae contributes to the eutrophication process in a water body [13]. The ammonia nitrogen concentrations ranged between a minimum of 0.31 mg/L in 2008 and a maximum of 1.85 mg/L in 2016.…”
Section: Concentration Of Water Quality Parameters In Kedah Rivermentioning
confidence: 99%
“…The nitrogen compound is a fertilizer that can induce algal boom, lowering oxygen levels in the water, while ammonia-nitrogen is harmful to marine organisms [114]. Ammoniacal nitrogen has been listed as one of the major contaminants polluting several rivers, that is contribute to the eutrophication mechanism is used to assess the water quality [115]. Temperature rises will degrade lake water quality by lowering hypolimnetic dissolved oxygen concentrations and increasing mineralization and nitrogen release from lake bottom sediments.…”
Section: Nitrogenmentioning
confidence: 99%